Moderation of Human Resource Competencies in Quality of Financial Statements: Application of Government Accounting Standards, Utilization of Information Technology, and Control Environment - Yamin, Nina Yusnita; Lawaidjo, Muhammad Rizki; ., Ridwan (Journal of Ecohumanism, 2025)
This study aims to examine and analyze the important role of human resource competence as a determinant of the quality of financial statements. In addition, this study also analyzes the effect of the application of government accounting standards, the use of information technology, and the control environment on the quality of financial statements. Sampling is based on the saturated sampling technique (census) with a total sample size of 120 samples. Respondents in this study were the Head of the Finance Subdivision, the Regional Government Information System (SIPD) Operator, and the Spending Treasurer at the Regional Apparatus Organization (OPD) of the Central Sulawesi Provincial Government. The analysis method used is Structural Equation Modeling (SEM) analysis and uses the warppls 7.0 application. The results of this study indicate that the application of government accounting standards contributes positively to the quality of financial statements. However, the use of information technology and the control environment do not have a significant effect on the quality of financial statements. Interestingly, human resource competence does not show significant results as a moderating variable. This study provides implications for efforts to improve the quality of government financial reports. Especially in developing the competence of Human Resources, especially in the fields of accounting and information technology.